Transcriptome analysis of root‐knot nematode (Meloidogyne incognita)‐infected tomato (Solanum lycopersicum) roots reveals complex gene expression profiles and metabolic networks of both host and nematode during susceptible and resistance responses. (24th April 2017) - Shukla, Neha; Yadav, Rachita; Kaur, Pritam; Rasmussen, Simon; Goel, Shailendra; Agarwal, Manu; Jagannath, Arun; Gupta, Ramneek; Kumar, Amar
Summary: Root‐knot nematodes (RKNs, Meloidogyne incognita ) are economically important endoparasites with a wide host range. We used a comprehensive transcriptomic approach to investigate the expression of both tomato and RKN genes in tomato roots at five infection time intervals from susceptible plants and two infection time intervals from resistant plants, grown under soil conditions. Differentially expressed genes during susceptible (1827, tomato; 462, RKN) and resistance (25, tomato; 160, RKN) interactions were identified. In susceptible responses, tomato genes involved in cell wall structure, development, primary and secondary metabolite, and defence signalling pathways, together with RKN genes involved in host parasitism, development and defence, are discussed. In resistance responses, tomato genes involved in secondary metabolite and hormone‐mediated defence responses, together with RKN genes involved in starvation stress‐induced apoptosis, are discussed. In addition, 40 novel differentially expressed RKN genes encoding secretory proteins were identified. Our findings provide novel insights into the temporal regulation of genes involved in various biological processes from tomato and RKN simultaneously during susceptible and resistance responses, and reveal the involvement of a complex network of biosynthetic pathways during disease development.